2020
DOI: 10.1016/j.jen.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Examination of the Factors Related to Emergency Nurses’ Motivation to Protect Themselves Against an Ebola Infection

Abstract: The current literature on protection motivation indicates only approximately 40% of emergency nurses felt prepared to provide care to patients potentially infected with Ebola virus. This article contributes to the understanding of protection motivation. Our study found that response efficacy and self-efficacy predicted emergency nurses' proactive protection motivation and perceived vulnerability, response cost, and knowledge predicted their passive protection motivation. Key implications for emergency nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
6
8
3
1
Order By: Relevance
“…Based on the present results, the coping appraisal variables were the strongest predictors of protective behaviors in the target population. In line with several previous studies [ 28 , 46 ], self-efficacy was the strongest predictor of these behaviors, followed by response efficacy. It seems that individuals with a higher level of self-efficacy perceive themselves to be capable of achievements; therefore, they show a tendency toward preventive behaviors of COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the present results, the coping appraisal variables were the strongest predictors of protective behaviors in the target population. In line with several previous studies [ 28 , 46 ], self-efficacy was the strongest predictor of these behaviors, followed by response efficacy. It seems that individuals with a higher level of self-efficacy perceive themselves to be capable of achievements; therefore, they show a tendency toward preventive behaviors of COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…Self-e cacy was the strongest predictor of the behavior. Only next was the response e cacy, similar to several other studies (21,37) .Those enjoying a higher level of self-e cacy perceive themselves capable of making achievements. Thus, they show a tendency to preventive behaviors of the disease.…”
Section: Resultssupporting
confidence: 78%
“…Other researchers have also shown that observational learning can enhance outcome expectations and can in uence behavior (30). Contrary to these results, in another study that showed the results of predicting the constructs of protection motivation theory integrated with the outcome expectation construct of the social cognitive theory related to protective measures against Ebola infection, the outcome expectation construct did not predict the protective behaviors of nurses against Ebola infection (31).…”
Section: Discussioncontrasting
confidence: 65%